Relationship between clinical signs and hormonal analytical findings in bitches with lactatio sine graviditate - Ganz, Sebastian; Olschewski, Carla; Failing, Klaus; Bostedt, Hartwig (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Objective Lactatio sine graviditate of the bitch can become clinically relevant in particularly severe manifestations. The aim of the study was to relate the hormone pattern consisting of progesterone (P4), estradiol 17β (E2) and prolactin to the time of occurrence of lactatio sine graviditate in the course of metoestrus and anoestrus as well as to its symptomatology.Material and methods Sixty-eight bitches with apparent lactatio sine graviditate were divided into 3 groups according to their cycle status. All bitches were examined for gynaecological findings. Furhtermore, their blood progesterone, oestrogen, and prolactin concentrations were determined and compared with the 133-day hormone profile of 7 control animals.Results Lactatio sine graviditate occurring in early metoestrus was characterised more by a shifted P4:E2 ratio than by hyperprolactinaemia. Overall, the prolactin concentration in the peripheral blood was significantly increased. Analysis of the individual cases revealed that hyperprolactinaemia was present to varying degrees. It could be detected in almost all bitches that showed full symptomatology at the end of metoestrus or at the beginning of anoestrus. Only then clinical signs correlated with an increased prolactin concentration in the peripheral blood. In most cases, the estradiol-17β concentration was within the reference range.Conclusion and clinical relevance The study indicates that the administration of prolactin inhibitors alone is not indicated in all cases of lactatio sine graviditate and that the timepoint of onset of the clinically relevant symptoms and the current prolactin level should be taken into account in the treatment of affected bitches.
Keywords: Lactatio falsa; hormone profile; prolactin; progesterone; oestradiol